Zimowe utrzymanie dróg w świetle prawa polskiego = Winter road maintenance in the light of national law - Czarna, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Basics activities which are conducted by road services within maintaining the roads in winter, include removal of snow and winter slippery from the road surfaces. These activities are conducted with the use of roughing materials or melting agents for deglazing the road or with use of both methods jointly. In view of to the growing during the winter risks of snow and icing sidewalks and streets, including costs associated with winter maintenance and environmental costs (maintenance of roadside green) issues related to winter road maintenance regulated by a variety of acts.
Keywords: zimowe utrzymanie dróg; akty prawne; środki chemiczne; winter road maintenance; legislation; chemicals